Coping with institutional complexity: Intersecting logics and dissonant visions in a nation-wide healthcare IT implementation project. Issue 1 (30th May 2019) - Bunduchi, Raluca; Tursunbayeva, Aizhan; Pagliari, Claudia
Abstract : Purpose: Digital transformation projects are complex, lengthy and difficult to implement, often failing to meet their objectives. Previous research has attributed this failure to competing institutional logics influencing actors' coping responses, and differences in actors' interpretations of the project's goals, technology and processes - their "organising vision". The purpose of this paper is to analyse a complex technology implementation project from an institutional perspective, to further elucidate the role of multiple logics and organising vision. Design/methodology/approach: A qualitative single study approach was used to investigate a public-sector technology project aimed at delivering a unified Human resource information system (HRIS) across regional health organisations in one country. Findings: Four logics characterised the project (public sector, professional, corporate and market), but their relative dominance shifted as the project transitioned through stages, from comprehension to implementation. These shifts exposed tensions between components of actors' organising vision, which influenced their coping behaviours in response to unexpected changes in the project's strategic ambitions and technological scope. Coherence of vision, both within groups of actors and between them, was a key mediator of coping responses and project outcomes. Originality/value: This analysis demonstrates the role of actors' organising vision in bridging institutional logics and coping responses to shape digital transformation projects. It highlights the need to account not only for diverse institutional logics, but also for their changing influence as projects unfold and actors' attention is directed onto different aspects of the organising vision. From a management perspective, it illustrates the importance of clear and consistent communication, to avoid entrenching conflicting interpretations.